2012
DOI: 10.3109/01612840.2011.653037
|View full text |Cite
|
Sign up to set email alerts
|

The Paradox of Being Both Needed and Rejected: The Existential Meaning of Being Closely Related to a Person with Bipolar Disorder

Abstract: The aim of this study was to elucidate the existential meaning of being closely related to a person with bipolar disorder. A qualitative, descriptive, and explorative design with a phenomenological meaning-oriented analysis was used. The findings reveal a paradoxical, existential exposure of close relatives to a person with bipolar disorder, being both needed and rejected whilst being overshadowed by the specific changeable nature of bipolar disorder. Psychiatric health care services are recommended to conside… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“…Some aspects of good practice guidelines (Barker, Pistrang & Elliott, 2016;Elliott, Fischer & Rennie, 1999) do not seem to have been adhered to, such as disclosure of the researcher's perspective (Granek et al, 2016;Jönsson et al, 2011;Maskill et al, 2010;Rusner et al, 2012;Tranvag & Kristokkerson, 2008); and the carrying out of credibility checks through 'analytic auditing' (Rusner et al, 2012Tranvag & Kristokkerson, 2008 or 'testimonial validity' (Jönsson et al, 2011;Maskill et al, 2010;Rusner et al, 2012). These limitations reduce the confidence that can be placed in their findings.…”
Section: Department Of Health (2014mentioning
confidence: 99%
See 2 more Smart Citations
“…Some aspects of good practice guidelines (Barker, Pistrang & Elliott, 2016;Elliott, Fischer & Rennie, 1999) do not seem to have been adhered to, such as disclosure of the researcher's perspective (Granek et al, 2016;Jönsson et al, 2011;Maskill et al, 2010;Rusner et al, 2012;Tranvag & Kristokkerson, 2008); and the carrying out of credibility checks through 'analytic auditing' (Rusner et al, 2012Tranvag & Kristokkerson, 2008 or 'testimonial validity' (Jönsson et al, 2011;Maskill et al, 2010;Rusner et al, 2012). These limitations reduce the confidence that can be placed in their findings.…”
Section: Department Of Health (2014mentioning
confidence: 99%
“…Family members' experiences of being excluded or over-looked by services have been well-documented (Rowe, 2012;Rusner et al, 2012, Tranvag & Kristoffersen, 2008. Studies of severe mental health problems carried out in the UK have also highlighted issues raised in this study, such as confidentiality being used inflexibly, and an absence of crisis planning, suggesting these difficulties are particularly pertinent to the British system of care (Chatzidamianos et al, 2015;Wainwright et al, 2015).…”
Section: The Challenges Of Supporting a Family Member With Bipolar DImentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies related to persons living with BD (Rusner et al . 2009; 2010) and one study related to close relatives (Rusner et al . 2012) have been published so far.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of qualitative studies have set out to examine aspects of bipolar disorder that do not lend themselves easily to quantitative research. Some of these studies related to the experience of the patient , while others focused on the experience of caregivers and/or close relations . Quantitative research on bipolar disorder has indicated that divorce and separation are two to three times more likely than in the general United States population and the risk of suicide in patients is high, estimated to be close to 20% .…”
mentioning
confidence: 99%